Network motifs: basic building blocks of biological networks - Alon, Uri (Henry Stewart Talks, 2012)
Complex networks are found throughout biology, Can we define the basic building blocks of networks?, Database of direct transcription interactions in E. coli, Algorithm that finds n-node network motifs, Feedforward loop (FFL), Dynamics of the feed-forward loop system, The feed-forward loop is a filter for transient signals allowing fast shutdown, GFP reporter plasmid system for promoter activity, Response to brief pulses of X is filtered by FFL, Sign-sensitive filtering by arabinose feed-forward loop, Single input module (SIM), Dense overlapping regulons (DOR), Incoherent FFL is a pulse generator, Network motifs in human organ development, Network motifs in growth factor signalling, High-accuracy promoter activity measurements in living cells